#MeToo on the Canadian Prairies: Raising Awareness of Sexual Assaults and Mental Health in Women Abused by Intimate Partners - Tutty, Leslie M. (Violence against women, 2022)
Studies of intimate partner sexual assault (IPSA) and its effects on mental health are limited. This secondary data analysis examines IPSA, a history of child sexual abuse, depression, trauma, mental distress and quality of life in 665 Canadian women, 41% of whom had been sexually assaulted by intimate partners; 53% were sexually abused as children. Women who had experienced any IPSA had significantly higher scores on all Composite Abuse subscales (IPV), mental distress (SCL-10), and depression (CES-D-10). PTSD (PCL) was higher for women with both IPSA and CSA histories. Implications for advocates, clinicians, and researchers are presented.